The first report of dark septate endophytes from Indonesian Pinus merkusii and its symbiosis role as a plant growth promoter in nursery condition - JUMADIL AKHIR; ELIS NINA HERLIYANA; SURONO SURONO; SRI WILARSO BUDI (Society for Indonesian Biodiversity, 2024)
Abstract. Akhir J, Herliyana EN, Surono, Budi SW. 2024. The first report of dark septate endophytes from Indonesian Pinus merkusii and its symbiosis role as a plant growth promoter in nursery condition. Biodiversitas 25: 312-321. To encourage the healthy growth of Pinus merkusii Jungh et de Vriese seedlings at the seedling stage, Dark Septate Endophytic (DSE) fungi were used as growth promoters. In this study, four DSE strains, i.e., Apls 1.5.3, Pls 32.1, Hs14.6a, and Hs14.6c isolated from P. merkusii roots, were tested for their ability to stimulate the growth of P. merkusii seedlings. After 14 weeks of incubation in nursery conditions, P. merkusii seedlings inoculated with four DSE strains experienced a higher increase in height and stem diameter when compared to the control treatment. Overall, the biomass results of P. merkusii seedlings treated with the DSE strains performed better than those of the control. Root colonization of P. merkusii seedlings showed that the 4 DSE strains significantly outperformed the control. The Hs14.6c strain outperformed the other strains and controls regarding nutrient (nitrogen) uptake. The findings of this study are the first to show that the DSE Apls 1.5.3 strain is similar to Cylindroccarpon, the Hs14.6a and Hs14.6c strains are similar to Cladophialophora sp., and the Pls 32.1 strain is similar to Oncopodiella trigonella based on identification results and phylogenetic trees and can be in symbiosis with seeds of P. merkusii, a pine species native to Indonesia.